Zero-Free Sets in Abelian Groups - Vahe G. Sargsyan (Изд-во НАН РА)
The subset A of the group G is called zero-free if the equation x+y+z=0 has no solutions in the set A: The upper and lower estimates were obtained for the maximum cardinality of the zero-free set in an Abelian group, and the asymptotic behavior of the logarithm of the number of zero-free sets in an Abelian group was established. Keywords: Sum-free set, Characteristic function, Group, Progression, Coset.
Keywords: Mathematics